Combined atom probe tomography and density functional theory investigation of the Al off-stoichiometry of κ-carbides in an austenitic Fe–Mn–Al–C low density steel. (March 2016) - Yao, M.J.; Dey, P.; Seol, J.-B.; Choi, P.; Herbig, M.; Marceau, R.K.W.; Hickel, T.; Neugebauer, J.; Raabe, D.
Abstract: We report on the investigation of the off-stoichiometry and site-occupancy of κ-carbide precipitates within an austenitic (γ), Fe-29.8Mn-7.7Al-1.3C (wt.%) alloy using a combination of atom probe tomography and density functional theory. The chemical composition of the κ-carbides as measured by atom probe tomography indicates depletion of both interstitial C and substitutional Al, in comparison to the ideal stoichiometric L′12 bulk perovskite. In this work we demonstrate that both these effects are coupled. The off-stoichiometric concentration of Al can, to a certain extent, be explained by strain caused by the κ/γ mismatch, which facilitates occupation of Al sites in κ-carbide by Mn atoms (Mn γ Al anti-site defects). The large anti-site concentrations observed by our experiments, however, can only be stabilized if there are C vacancies in the vicinity of the anti-site. Graphical abstract: Atom probe tomography measurements have been performed to determine the composition of κ-carbides, which is important for the hardening effect of these precipitates in Fe–Mn–Al–C quaternary alloys. We observe a systematic off-stoichiometric Al content, which is analysed in combination with density functional theory calculations. We reveal that an intriguing combination of elastic strain minimization by anti-site defects and C vacancies in their vicinity can explain this phenomenon.